The Use of Computational Approaches in the Discovery and Mechanism Study of Opioid Analgesics - Zhao, Bangyi; Li, Wei; Sun, Lijie; Fu, Wei (Frontiers in Chemistry, 2020)
G-protein-coupled receptors (GPCRs) consists of the most therapeutic targets that aimed approximately 40% of modern medicinal drugs. Understanding the agonist/antagonist mechanism, as well as the signal transduction mechanism of the GPCRs, is important in drug discovery. In the past few years, determination of high-resolution crystal structures of GPCRs from different subfamilies laid a solid basis for both experimental and computational studies on GPCR-related diseases. Opioid receptors that belong to class A GPCRs are vital in pain control. As a robust approach, computer-aided drug design (CADD) has been regarded as a powerful tool to discover novel leading compounds and to help understand the activation mechanism of related receptors. Herein, we reviewed the recent progresses on CADD-based drug discovery, basis for receptor subtype selectivity, agonist mechanism and biased signaling mechanism in opioid receptors.